About the nature of diffusion anisotropy in CdS crystals - Borkovskaya, L.V.; Dzhumaev, B.R.; Khomenkova, L.Yu.; Korsunskaya, N.E.; Markevich, I.V.; Sheinkman, M.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Electrodiffusion of copper into nominally undoped high-resistivity CdS crystals at 250-400°C has been investigated. A strong diffusion anisotropy has been observed, copper diffusion in perpendicular to the c-axis direction being more than one order faster as compared with its diffusion in parallel to the c-axis direction. The effect has been shown to be not due to greater density of perpendicular to the c-axis dislocations than that of parallel to the c-axis ones, as it was thought earlier. Electrically active dislocations lying in the basal plane are supposed to be channels of fast diffusion owing to their intensive decoration with intrinsic defects and residual impurities.